Cytopathologic Diagnosis in Pleural Effusion and Cyto-Histopathologic Correlation - Dagli, Adile Ferda; Kucuk, Sirin; Sezer, Muge; Ucer, Ozlem (Federation Turkish Pathology Soc, 2011)
Objective: Cytological examination of pleural fluids is a fast, efficient and non-invasive diagnostic method. Identification of malignant effusions bears critical importance in treatment and prognosis. The aim of this study was to investigate the distribution of cytopathologic diagnoses in pleural effusions and the cyto-histopathologic correlation rates. Material and Method: A total of 298 pleural fluid cases diagnosed from 2008 to 2009 in our laboratory were retrospectively identified as the study group. Evaluation results were classified in 5 groups as inconclusive, benign, atypical, suspicious and malignant, and compared with the biopsy results. Results: Of the total 298 pleural fluid cases, 114 (38.3%) were females and 184 (61.7%) were males. The age range was between 15 and 89 with a mean value of 58.4 +/- 17.8. Of the cases, 3 (1%) were diagnosed as inadequate, 246 (82.6%) benign, 8 atypical, 10 suspicious, and 31 malignant by cytology. Among the cases who were diagnosed as malignant, 24 (8.1%) were reported as metastatic carcinoma and 7 (2.3%) as malignant mesothelioma. Of the 8 cases reported as atypical, biopsy results of 2 showed malignant mesothelioma, and of the 10 cases reported as suspicious, 1 case whose biopsy result was obtained was diagnosed as epidermoid carcinoma metastasis. Conclusion: Cytological examination is the most valuable diagnostic method for pleural effusions which may have various etiological causes. The most common cause of pleural effusions in our region is metastatic carcinomas including those from the lung, breast and ovarian tumors, followed by malignant mesothelioma.
Keywords: Pleural effusion; Cytopathology; Histopathology